Locating intercalants within lipid bilayers using fluorescence quenching by bromophospholipids and iodophospholipids. (July 2019) - Alexenberg, Carmit; Afri, Michal; Eliyahu, Shlomi; Porat, Hani; Ranz, Ayala; Frimer, Aryeh A.
Graphical abstract: Schematic model for the location of resorufin, PP3 and PP7 within liposomal bilayer using KBr and bromophospholipid quenching. Highlights: Measuring the depth of intercalated molecules within the lipid bilayer is of importance in understanding reactivity. 13 C NMR, fluorescence, and the ESR techniques have been previously used. We have synthesized phospholipids with bromine or iodine at various positions along the lipid chain. The halolipids were intercalated in turn with various fluorophores into DMPC liposomes, biomembranes and erythrocyte ghosts. The most effective fluorescence quenching occurs when the heavy atom location corresponds to that of the fluorophore. Abstract: In previous work, we have been able to determine the depth of intercalated molecules within the lipid bilayer using the solvent polarity sensitivity of three spectroscopic techniques: the 13 C NMR chemical shift (δ); the fluorescence emission wavelength (λem ), and the ESR β-H splitting constants (aβ-H ). In the present paper, we use the quenching by a heavy atom (Br or I), situated at a known location along a phospholipid chain, as a probe of the location of a fluorescent moiety. We have synthesized various phospholipids with bromine (or iodine) atoms substituted at various locations along the lipid chain. The latter halolipids were intercalated in turn with various fluorophores into DMPC liposomes, biomembranes and erythrocyte ghosts. The most effective fluorescence quenching occurs when the heavy atom location corresponds to that of the fluorophore. The results show that generally speaking the fluorophore intercalates the same depth independent of which lipid bilayer is used. KBr (or KI) is the most effective quencher when the fluorophore resides in or at the aqueous phase. Presumably because of iodine's larger radius and spin coupling constant, the iodine analogs are far less discriminating in the depth range it quenches.